(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
In this research paper, we examine the characteristics of the mechanism by which science reaches a discursive culture external to the science sector. In order to help students understand a set of concepts and technological and empirical processes (scientific), we examine the oral discourse developed in the classroom through interaction. The teacher must aim to create small scientists curious about what surrounds them. The school plays a key role in consolidating this cognitive framework of science in the psychological constructions of students, but so do the media and families. We research the interactive mechanisms for the assimilation of said information, based on a compilation of transcripts in the classroom of the oral discourse.